THE CONDITION OF CORAL REEFS IN WEST BANGKA WATER - Siringoringo, Rikoh Manogar; Hadi, Tri Aryono (Marine Research in Indonesia, 2014)
Bangka Island is well known as the worldÃ¢â¬â¢s largest tin producer. The inland and offshore tin mining hasÃÂ profound effects on the coastal environment, resulting in the high sedimentation in the water. Many corals sufferedÃÂ physiological damage due to low light intensity. The distribution of stony corals and the status of coral reefs wasÃÂ surveyed at 6 sites in West Bangka waters in October 2012. A total of 72 species of corals belonging to 33 generaÃÂ and 12 families were found, and 4 species were distributed at all research sites. The live coral coverage was 36% on average and was categorized as being in fair condition. The coverage was 0% at Kamboja Island where the coralsÃÂ were the most affected by tin mining. The sediment flowed out from tin mining, blocked the light, and settled onÃÂ the coralsÃ¢â¬â¢ surface. Consequently, many corals were buried and the live corals decreased. It is obviously necessaryÃÂ to reduce and control the tin mining.